Crop diversification and small holders: A micro-level evidence from Uttar Pradesh - DUBEY, S K; SINGH, A K; SINGH, LAKHAN; SINGH, ATAR; KANAUJIA, V K; SINGH, BHUPENDRA KUMAR (The Indian Journal of Agricultural Sciences, 2020)
Survey was conducted in villages Digsara, Basirpur Mar, Pokhra and Bhavanipur under Jalalabad block of Kannauj districts to analyze the crop diversification systems during 2015–16. The major cropping systems included potato-groundnut/maize; paddy-potato-maize; paddy-wheat-green manuring; groundnut/maize-potato-maize; maizemustard- maize and green manuring-early potato-wheat/seed potato. It was observed that summer groundnut was fast replaced by summer maize despite higher water requirement in summer maize (6–7 irrigation) than groundnut (3–4 irrigation) as farmers were getting higher yield (60–70 q/ha) in summer maize than groundnut (Yield: 37–40 q/ ha).Summer groundnut was perceived more sustainable than summer maize as the underground water level was fast depleting in these area (declining at the rate of 2 ft. every year). Wheat crop was getting marginalized among small land holders. Major cropping systems followed by such farmers were fallow/dhaincha-potato-maize; maize-potatomaize and maize-early potato-wheat (very less area). Diversification with mixed cropping of minor vegetables likes coriander and kharif onion was also analyzed in these districts. Flower cultivation based crop diversification was documented in this study. It was found that flowers like rose, bela (jasmine) and mehndi (henna) were cultivated by the majority of farmers to address the industrial requirements in the district for making edible products of roses as well as perfumes. Potato+rose was the most frequently utilized cropping pattern as the fertilizer requirements of roses were being met from the residual nutrients of potato.The study recommends that the diversity in cropping systems among the small holders ought to be safeguarded and supported with the appropriate development interventions.